Motivation for Digital Activism on Instagram Among Postgraduate Students Amidst The Impact of Misinformation, Malinformation, and Disinformation - Zaki Khudzaifi Mahmud (Journal of Social Research, 2025)
The shift of activism from the real world to the digital world has intensified year by year, driven by social phenomena at both national and global levels. The existence of misinformation, malinformation, and disinformation certainly distorts the general public's ability to participate in digital activism activities. This study aims to examine the factors that motivate the educated general public to engage in digital activism activities on Instagram, as well as their discretion regarding the presence of misinformation, malinformation, and disinformation. Through a semi-structured interview process, it was found that the factors motivating individuals to participate in digital activism include the desire to increase public awareness or vigilance, as well as to educate the public about social issues considered important. In responding to non-credible information, the criticality and willingness of individuals to conduct research on social issues they wish to address play a crucial role.